2011
DOI: 10.1111/j.1464-410x.2010.09628.x
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between clinical and pathological stage: external validation of the impact on prognosis in an international radical cystectomy cohort

Abstract: • Up staging to muscle invasive disease occurred in 45.9% (n = 592) of 1,291 patients with clinical ≤ T1, including 30.6% of patients with Tis only at transurethral resection.• Of the 3,166 patients with clinically organ confined (OC) tumor stage, 1,357 (42.9%) were up staged to non-organ confined pathologic tumor stage.• Within each clinical stage stratum, patients who were clinically under staged had a higher probability of disease relapse or death from UCB compared to those who were same staged or down stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
114
1
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(128 citation statements)
references
References 21 publications
2
114
1
11
Order By: Relevance
“…24 Discrepancies between clinical and pathological staging is a major issue in MIBC with upstaging post-cystectomy occurring in almost 30% to 61% of cases. 16,[25][26][27] One of the strongest risk factors for upstaging is T2-disease. [25][26][27] As 20% to 30% of patients with pT2 disease relapse distantly and the SWOG-8710 trial reported a median 30-month improvement in overall survival with NC in patients with T2-tumours, there is a strong rationale to use NC even in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Discrepancies between clinical and pathological staging is a major issue in MIBC with upstaging post-cystectomy occurring in almost 30% to 61% of cases. 16,[25][26][27] One of the strongest risk factors for upstaging is T2-disease. [25][26][27] As 20% to 30% of patients with pT2 disease relapse distantly and the SWOG-8710 trial reported a median 30-month improvement in overall survival with NC in patients with T2-tumours, there is a strong rationale to use NC even in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…16,[25][26][27] One of the strongest risk factors for upstaging is T2-disease. [25][26][27] As 20% to 30% of patients with pT2 disease relapse distantly and the SWOG-8710 trial reported a median 30-month improvement in overall survival with NC in patients with T2-tumours, there is a strong rationale to use NC even in these patients. 6,22 An alternate strategy is to use a risk-stratified approach, in which patients with high-risk features receive NC and lowrisk patients who are upstaged receive adjuvant chemotherapy (AC).…”
Section: Discussionmentioning
confidence: 99%
“…Faktörlerin Araştırılması" -Dr. Polat Türker Mesane tümörlerinde, radikal sistektomi sonrası evre yükselmesi sık izlenen bir problem olup klinik ve patolojik evrenin birbirleri ile uyumlu rapor edilmesi yani doğru klinik evreleme ancak %20-%80 oranında sağlanabilmektedir (4). Klinik evreleme ile T2-T4a N0M0 saptanan hastalıkta neoadjuvan kemoterapinin uygun hastalarda sağkalım avantajı sağladığı gösterilmiştir (1).…”
Section: "Değişici Epitel Mesane Tümörü Hastalarında Klinik Ve Patolounclassified
“…While nearly half of the cases is understaged, 32% to 43% of the patients with clinically organ-confined (OC) (≤T2) bladder tumors are upstaged to nonorgan-confined pathological stage (NOC) (≥T3) at the time of RC. [3][4][5] Upstaging at the time of RC is associated with poor prognostic factors such as short disease-specific survival and higher risk for disease recurrence. [5,6] Beyond that patients with stage T2 bladder tumors who are subsequently upstaged at the time of cystectomy can potentially benefit mostly from neoadjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Upstaging at the time of RC is associated with poor prognostic factors such as short disease-specific survival and higher risk for disease recurrence. [5,6] Beyond that patients with stage T2 bladder tumors who are subsequently upstaged at the time of cystectomy can potentially benefit mostly from neoadjuvant chemotherapy. [7] But the inability to identify such patients at the outset weakens its potential advantage, as documented by a modest 5% absolute 5-year overall survival benefit.…”
Section: Introductionmentioning
confidence: 99%